Dual-Platform Large Along-Track Baseline GMTI - Baumgartner, Stefan V.; Krieger, Gerhard (IEEE Transactions on Geoscience and Remote Sensing, 2016)
In this paper, a novel method for traffic monitoring using a spaceborne dual-platform synthetic aperture radar system is presented. The chosen along-track baseline between both platforms needs to be on the order of ten to several tens of kilometers, resulting in a time lag of several seconds between the target observations. With the proposed method, the true geographical positions, the velocities, and the moving directions of the detected moving targets can be estimated with high accuracy. The method has been verified and evaluated using experimental data acquired with the German TerraSAR-X/TanDEM-X radar satellite formation. The results are compared with ground truth reference data.
DLR Import::2019-04-02
Keywords: Marine traffic control; Radar detection; Radar signal analysis; Radar signal processing; Radar velocity measurement; Remote sensing; Spaceborne radar; Synthetic aperture radar (SAR); Traffic information systems